Production of biodiesel using palm oil - Lam, M.K. (Elsevier, 2019)
For the past few years, advance research and development on biofuels production from renewable sources has been vehemently growing due to excessive burning of fossil fuel that caused several environmental issues, such as global warming. In addition, unstable petroleum price in the global market has accelerated the expansion of renewable biofuel industry, especially countries with abundant of oil-bearing or sugar-based crops. The use of biodiesel has been widely recognized due to its significant contributions in the reduction of greenhouse gases emission, specifically in transportation sector. Up to date, biodiesel can be derived from various oil-bearing crops (edible or nonedible) such as soybean, rapeseed, palm, sunflower, Jatropha curcas, and microalgae. This chapter focuses on palm biodiesel conversion technologies, including homogeneous, heterogeneous, enzymatic, noncatalytic supercritical alcohol, and ultrasound transesterification. Besides, optimum conditions, advantages, and limitations for each of the technology are discussed in detail. It is hoped that this chapter can provide a platform to researchers, policy makers, and industrial planners to synergize the opportunity of palm biodiesel production. Â© 2019 Elsevier Inc. All rights reserved.